Analisis Pengaruh Penambahan Minor Aktinida Am-241 dan Np-237 pada Performa Sel Bahan Bakar Uranium Metalic U-10%wtZr - Norman, Muhamad Tauffan Hidayatullah; Monado, Fiber; Ariani, Menik (Jurnal Riset Fisika Indonesia, 2025)
Nuclear reactors are capable of producing electricity using nuclear fuel in a sustainable system. Despite its benefits, the combustion of nuclear fuel in a reactor produces fission products known as nuclear waste. One type of nuclear waste is minor actinide, minor actinide is included in burnable poison so it can be recycled as additional fuel. This research was conducted to analyze the effect of the addition of minor actinides Am-241 and Np-237 on the burn-up performance of the Uranium Metallic U-10%wtZr fuel cell in a Gas cool-Fast Reactor with S-CO2 gas coolant and stainless steel cladding material. SS-316. The fuel pin was designed to be cylindrical with a diameter of 1.4 cm and then tested by adding 0 – 8% minor actinide to the fuel. Calculations were carried out based on the neutron transport equation using the SRAC program which produces survey parameters : Kinf value, burn-up level, conversion ratio, and atomic density throughout the burn-up period of 120 years. The results show that there is a slight increase in the Kinf value for each minor actinide addition at the beginning to the end of the burn-up period. The total atomic density of Am-241 and Np-237 in the fuel added with minor actinides decreased as the burn-up period ended. The addition of minor actinides did not have a significant effect on the neutronic performance of U-10%wtZr fuel but was able to reduce the amount of Am-241 and Np-237 elements at the end of the burn-up period.